2006
DOI: 10.1016/j.jpainsymman.2005.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Cluster Research: Conceptual, Design, Measurement, and Analysis Issues

Abstract: Abstract:Cancer patients may experience multiple concurrent symptoms caused by the cancer, cancer treatment, or their combination. The complex relationships between and among symptoms, as well as the clinical antecedents and consequences, have not been well described. This paper examines the literature on cancer symptom clusters focusing on the conceptualization, design, measurement, and analytic issues. The investigation of symptom clustering is in an early stage of testing empirically whether the characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
212
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(226 citation statements)
references
References 45 publications
6
212
0
5
Order By: Relevance
“…Rather than using factor or cluster analysis to group "similar" or "related" symptoms (factors) [5][6][7]9,10,17,35], the current study utilized cluster analysis to identify patient subgroups (distinct, mutually exclusive subgroups) that were defined by a similar symptom experience [12][13][14][15]19,22,23]. Given that symptom cluster research is still in its infancy in oncology [17], it is likely that both approaches may contribute unique insights to symptom burden analysis and possibly inform development of more effective symptom intervention approaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather than using factor or cluster analysis to group "similar" or "related" symptoms (factors) [5][6][7]9,10,17,35], the current study utilized cluster analysis to identify patient subgroups (distinct, mutually exclusive subgroups) that were defined by a similar symptom experience [12][13][14][15]19,22,23]. Given that symptom cluster research is still in its infancy in oncology [17], it is likely that both approaches may contribute unique insights to symptom burden analysis and possibly inform development of more effective symptom intervention approaches.…”
Section: Discussionmentioning
confidence: 99%
“…To that end, psychometric symptom assessment instruments have been developed [1][2][3] to help detect these symptoms and guide symptom management. Previous studies have shown that cancer patients experience multiple concurrent symptoms that may be characterized as symptom clusters [3][4][5][6][7][8][9][10]. In addition, studies have shown that the number or intensity of symptoms reported by patients is correlated with their perception of quality of life (QOL) [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, all of the prior studies examined symptoms as independent factors. Because many symptoms may be highly inter-related, the most appropriate method for studying the relationship between multiple concurrent symptoms and health outcomes remains unclear (7). The techniques of factor and principal component analysis have been utilized to cluster symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, an emerging body of research has turned attention to the study of symptom clusters (Barsevick, 2007;Barsevick, Whitmer, Nail, Beck, & Dudley, 2006;Bender, Ergun, Rosenzweig, Cohen, & Sereika, 2005;Chen & Lin, 2007;Dodd, Cho, Cooper, & Miaskowski, 2010;Fan, Filipczak, & Chow, 2007;H. Kim, Barsevick, Tulman, & McDermott, 2008;Miaskowski & Aouizerat, 2007;Molassiotis, Wengstrom, & Kearney, 2010;Ridner, 2005;Thornton, Andersen, & Blakely, 2010;Xiao, 2010).…”
Section: Symptom Clusters In Cancermentioning
confidence: 99%